The Relationship between Earnings Management, Financial Transparency, and Auditor Independence on Investor Trust - Halim, Indra; Prakoso, Teguh; Mubarok, Ahmad Zaki; Rachmani, Ferlinda Ainur; Sudarmanto, Eko (West Science Accounting and Finance, 2025)
This study investigates the relationship between earnings management, financial transparency, and auditor independence on investor trust in Indonesia. Using a quantitative research design, data were collected from 150 active investors through a questionnaire measured on a five-point Likert scale. The data were analyzed using SPSS version 25, employing descriptive statistics, validity and reliability testing, correlation analysis, and multiple regression. The results show that earnings management has a negative and significant effect on investor trust, indicating that manipulative reporting practices reduce investors’ confidence in financial information. In contrast, financial transparency and auditor independence both have positive and significant effects on investor trust, highlighting the importance of clear disclosures and professional audit integrity in strengthening investor confidence. Among the variables, financial transparency demonstrates the strongest influence, emphasizing its critical role in reducing information asymmetry and enhancing credibility. The study concludes that strengthening governance practices, improving reporting transparency, and ensuring auditor independence are essential strategies to enhance investor trust in Indonesia’s capital market.